2014
DOI: 10.4028/www.scientific.net/msf.803.120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solid/Liquid Ratio during Curing Time Fly Ash Based Geopolymer on Mechanical Property

Abstract: Geopolymer is produced from the alkali activation of materials rich in Si and Al such as fly ash. Based on the experimental and characterization result, solid to liquid ratio influenced the setting time and compressive strength of geopolymer in order to have good mechanical property. The optimum setting time and compressive strength were obtained at 3 : 1 solid to liquid ratio. Optimum curing time reach at 14 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…where they concluded that the ratio of the solid precursor to alkaline activator highly affects the workability, rheology, reactivity and setting time of geopolymer pastes during the synthesis. 23,59,60,62–66…”
Section: Resultsmentioning
confidence: 99%
“…where they concluded that the ratio of the solid precursor to alkaline activator highly affects the workability, rheology, reactivity and setting time of geopolymer pastes during the synthesis. 23,59,60,62–66…”
Section: Resultsmentioning
confidence: 99%
“…After the production of aggregates, it is subjected to different curing conditions as follows: (i) curing at ambient temperature (28 ± 2°C), (ii) heat curing at 80°C for 24 hours [15,23,24,27,42], and (iii) solution curing for 30 minutes [10] which will improve the properties of aggregates.…”
Section: Experimental Programmementioning
confidence: 99%
“…e alkali activator solution, which acts as an activator in the geopolymerisation process, plays an important role in the surface hydrolysis of the raw material particles [15]. e alkaline solution with different types [15][16][17][18][19], concentrations [16][17][18][19][20][21][22][23][24], raw material to solution ratio [17,[25][26][27], and curing regime [15,23,24,27,28] has a significant influence in the geopolymerisation process. However, there are a limited number of studies reported in the literature on the utilization of alkaline solutions for the production of artificial fly ash aggregates, whereas the factors responsible for fly ash aggregates production through pelletization process, combined with the factors of geopolymerisation, are very much essential to understand the efficient and effective production.…”
Section: Introductionmentioning
confidence: 99%
“…A 5-level-3-factor central composite design (CCD) was employed as in previous literature [22], which required 20 runs. V 1 , V 2 , and V 3 were the factors and each level was chosen based on literature [23][24][25] and preliminary laboratory work conducted, and these were within the allowed range of the composite coating material. A complete CCD and their coded and uncoded levels of the factors are given in Table 3.…”
Section: Experimental Designmentioning
confidence: 99%